From genetic variants to therapeutic targets: insights into understanding rheumatoid arthritis - Chen, Lu; Zhao, Jianan; Meng, Qingliang (Frontiers in Immunology, 2025)
Rheumatoid arthritis (RA) is a chronic inflammatory autoimmune disease that affects multiple systems and is driven by various factors, including interactions between genetic and environmental elements. Over the past few decades, genome-wide association studies (GWAS) have been instrumental in regard to identifying genetic and environmental risk factors associated with RA susceptibility and pathogenesis. The recent discoveries of novel genetic susceptibility loci and pathways offer promising therapeutic targets for RA and precision medicine. More than 100 genetic loci have been identified in RA patients. In this review, we have focused on more than 40 genes that have been supported by evidence to be closely associated with the development of RA. These include genes involved in various mechanisms, such as loss of self-tolerance, autoimmune antibody production (e.g., HLA-DRB1, HLA-DPB1), inflammatory signaling and bone destruction (e.g., PTPN22, CCR6), complication (e.g., HLA-DQB1, IRF5), and differential drug responses (e.g., HLA-E, NKG2D). These novel players and mechanisms enhance our understanding of the RA pathogenesis and also provide a reference for personalized and precise medicine, including diagnosis and treatment.